An investigation of irregular crack path effects on fracture mechanics parameters using a grain microstructure meshing technique - Mehmanparast, Ali; Biglari, F.; Davies, C. M.; Nikbin, Kamran (World Scientific Publishing, 2012)
A sub-grain size finite element modelling approach is presented in this paper to investigate variations in fracture mechanics parameters for irregular crack paths. The results can be used when modelling intergranular and transgranular crack growth where creep and fatigue are the dominant failure mechanisms and their crack paths are irregular. A novel method for sub-grain scale finite element mesh consisting of multiple elements encased in ~50–150 μm-sized grains has been developed and implemented in a compact tension, C(T), mesh structure. The replicated shapes and dimensions were derived from an isotropic metallic grain structure using representative random sized grain shapes repeated in sequence ahead of the crack tip. In this way the effects of crack tip angle ahead of the main crack path can be considered in a more realistic manner. A comprehensive sensitivity analysis has been performed for elastic and elastic-plastic materials using ABAQUS and the stress distributions, the stress intensity factor and the J-integral have been evaluated for irregular crack paths and compared to those of obtained from analytical solutions. To examine the local and macroscopic graph path effects on fracture mechanics parameters, a few extreme cases with various crack-tip angles have been modelled by keeping the macroscopic crack path parallel to the axis of symmetry. The numerical solutions from these granular mesh structures have been found in relatively good agreement with analytical solutions.
Electronic version of an article published as Journal of Multiscale Modeling, Vol. 4, Iss. 1, atricle 1250001, 2012, http://dx.doi.org/10.1142/S1756973712500011 © World Scientific Publishing Company, http://www.worldscientific.com/worldscinet/jmm
Keywords: Intergranular; Transgranular; Crack path; Grain; Microstructure